Environmental Education: A Strategy for Nature Preservation - Castillo, Verenice Sánchez (Journal of Ecohumanism, 2024)
Environmental education is an essential strategy for nature conservation. To this end, an analysis is needed to explore its impact from the perspective of scientific literature. This study was conducted using a bibliometric approach based on the analysis of articles published between 2019 and 2023 in the Scopus, Web of Science, and Google Scholar databases. The terms “environmental education” and “nature preservation” were analyzed. Indicators associated with the number of publications, collaboration networks, main trends, and keyword co-occurrence, among others, were taken into account. The VOSviewer software, the platform lens.org, and the bibliographic manager Zotero were used. Different authors addressing the topic, the institutions with the highest output, the fundamental keywords, and the interrelationship between the categories of conservation, sustainability, and critical pedagogy were identified. Among the most cited articles are those with community-based and participatory approaches. The analysis shows an increase in research on environmental education, although there are some longitudinal and comparative gaps between different regions. It concludes by stating that this field is moving towards interdisciplinary methodologies and has a high social component.